Analysis of Online Shopping Addiction Level Using the K-nearest Neighbor Algorithm at SMK Negeri 1 Tanjung Pura - Zulham Sitorus; Alviona Marsya; Desy Ramatika; Ramli S Siburian (Yayasan Sinergi Multidimensi Kreatif, 2024)
The rapid development of technology has significantly had an indirect impact on all aspects and dimensions of human life. Online shopping is a form of technological progress. Online shopping is all activities related to online transactions that take place via the internet or other electronic networks. The online shopping process no longer requires face-to-face contact but can be done simply by communicating via the internet. Based on the researcher's preliminary study, at SMK Negeri 1 Tanjung Pura many students spend time shopping online. This online shopping is not only done during break times or after school but is also done during class hours. Based on researchers' observations, students at SMK Negeri 1 Tanjung Pura who like online shopping have an impact on their education. Their study time is reduced, causing their grades to drop. Apart from that, online shopping affects its users, it can cause relational and social problems which have made children rarely socialize with their surroundings, withdraw from social interactions and ultimately make their lives uncontrollable because online shopping takes over their minds. Therefore, through this task, an analysis of the level of online shopping addiction was made using the K-Nearest Neighbor method. The data used is data from students at SMA Negeri 1 Tanjung Pura and the results of this data will be classified using the K-Nearest Neighbor algorithm to find out whether someone is addicted to online shopping based on the level of addiction. The results of the analysis of the level of online shopping addiction in these students, whether they have low addiction or high addiction.